Freshman learning communities, college performance, and retention - Julie L. Hotchkiss; Robert E. Moore; M. Melinda Pitts (Federal Reserve Bank of Atlanta, 2005)
This paper applies a standard treatment effects model to determine that participation in Freshman Learning Communities (FLCs) improves academic performance and retention. Not controlling for individual self-selection into FLC participation leads one to incorrectly conclude that the impact is the same across race and gender groups. Accurately assessing the impact of any educational program is essential in determining what resources institutions should devote to it.
Keywords: 330; Bildungsverhalten; Studium; Schätzung; USA